A tissue-engineered urinary conduit in a porcine urinary diversion model - Arkadiusz Jundziłł (Nature Portfolio, 2021)
Abstract The use of an ileal segment is a standard method for urinary diversion after radical cystectomy. Unfortunately, utilization of this method can lead to numerous surgical and metabolic complications. This study aimed to assess the tissue-engineered artificial conduit for urinary diversion in a porcine model. Tissue-engineered tubular polypropylene mesh scaffolds were used for the right ureter incontinent urostomy model. Eighteen male pigs were divided into three equal groups: Group 1 (control ureterocutaneostomy), Group 2 (the right ureter-artificial conduit-skin anastomoses), and Group 3 (4 weeks before urostomy reconstruction, the artificial conduit was implanted between abdomen muscles). Follow-up was 6 months. Computed tomography, ultrasound examination, and pyelogram were used to confirm the patency of created diversions. Morphological and histological analyses were used to evaluate the tissue-engineered urinary diversion. All animals survived the experimental procedures and follow-up. The longest average patency was observed in the 3rd Group (15.8 weeks) compared to the 2nd Group (10 weeks) and the 1st Group (5.8 weeks). The implant’s remnants created a retroperitoneal post-inflammation tunnel confirmed by computed tomography and histological evaluation, which constitutes urostomy. The simultaneous urinary diversion using a tissue-engineered scaffold connected directly with the skin is inappropriate for clinical application.